Nation-Building Governance and Its Criteria in the Public Structure of Afghanistan and India - Ensan Doost, Mohammad Saber; Shabannia Mansour, Mehdi; Baseri, Babak (Legal Studies in Digital Age, 2025)
Throughout history, various phenomena have influenced the process of nation-building in countries, and history bears witness to the fact that, in many cases, these elements have produced different reflections and consequences across the world. Accordingly, the present study, using a descriptive-analytical approach and relying on library and documentary research methods, seeks to examine how nation-building has occurred and to identify its criteria in the public structures of Afghanistan and India. The findings of this study indicate that despite the many similarities between the two countries—such as ethnic, cultural, religious, and linguistic diversity—the approaches to nation-building and their reflections in these two nations have been markedly different. According to the results, historically, India has a distinguished background in nation-building, rooted in the collective determination and mobilization of its people, as well as their persuasion and consensus, which has led to internal cohesion. In contrast, Afghanistan has never experienced such a grassroots movement from within its masses, nor have its leaders initiated a unifying national endeavor that could foster collective unity among the people. The final findings of this study confirm that elements such as the struggle against British colonialism and the restoration of independence, democracy, pluralism, and the political structure have each played significant—yet different—roles in shaping the process and method of nation-building in these two countries.